2010
DOI: 10.1163/22941932-90000012
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Ipê (Handroanthus SPP.) and Maçaranduba (Manilkara SPP.) Woods in the manufacture of bows for string instruments

Abstract: While the wood Caesalpinia echinata (pernambuco wood) is traditionally used in the manufacture of bows for string instruments, wood of other genera such as Handroanthus (syn. Tabebuia) and Manilkara are also used in bow making, but still on a very small scale. This study aims to evaluate the anatomical, chemical, physical, mechanical, and acoustic characteristics of these two latter woods, establishing their potential for bow making. Length, frequency of vessel elements and rays, and the higher percentage of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
7
1
3
Order By: Relevance
“…Alves et al (2008b) reported C. echinata wood showed about 60% of fibers, while that of Handroanthus spp. in the present study showed little difference at 55% of fibers (LONGUI et al, 2010b).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Alves et al (2008b) reported C. echinata wood showed about 60% of fibers, while that of Handroanthus spp. in the present study showed little difference at 55% of fibers (LONGUI et al, 2010b).…”
Section: Discussioncontrasting
confidence: 51%
“…, these results suggest that density is not homogeneous along the stick, and, therefore, the stick would not meet the standard (LONGUI et al, 2010b). In fact, bow manufacture would be difficult under these circumstances since heterogeneity would lead to sections of increased resistance to cutting instruments along the stick, thus making it more difficult to provide equilibrium to the bow.…”
Section: Discussionmentioning
confidence: 95%
“…Entre essas está a madeira de ipê (Handroanthus spp.) estudada por [51]. Fomin [32] obteve uma avaliação satisfatória por parte de músicos profissionais para arcos de alta qualidade construídos a partir de madeira de ipê.…”
Section: A Vareta: Materiais E Formaunclassified
“…Uma análise mais sofisticada [30,53] permite estabelecer um "índice de desempenho" (Performance Index -P I) para as madeiras usadas em arcos de instrumentos de cordas através da eq. (1), onde ρ é a densidade volumétrica da madeira.…”
Section: A Vareta: Materiais E Formaunclassified
See 1 more Smart Citation